Association between etiologic species with CD4 count and clinical features of oral candidiasis among HIV/AIDS patients - Dwi Murtiastutik; Cita R.S. Prakoeswa; Indah S Tantular; Muhammad Yulianto Listiawan; Afif N Hidayati; Evy Ervianti; Lunardi Bintanjoyo (Wolters Kluwer Medknow Publications, 2022)
Background Oral candidiasis (OC) is an oral mucosal disorder due to Candida genus. Its predisposing factor among patients with HIV/AIDS is mainly decreasing CD4 count. OC is commonly caused by Candida albicans. As CD4 decreases, the shift to C. non-albicans has been observed. Objective To evaluate the association of Candida species with CD4 count and clinical features in HIV/AIDS patients with OC. Patients and methods This is a cross-sectional study. A total of 114 oral rinse solution samples from HIV/AIDS patients with OC were collected. Candida species identification was done by culture in Chromagar followed by VITEK 2. The association of Candida species with CD4 count and clinical features was analyzed using Pearson's χ2 and Kruskal-Wallis tests. Results There was growth of 149 isolates in culture from 114 patients. C. albicans was found in 104 (69.7%) isolates. Candida non-albicans were found in 45 (30.3%) isolates, namely Candida krusei in 22 (14.85%), Candida glabrata in 12 (8.1%), Candida tropicalis in six (4.05%), Candida dubliniensis in two (1.3%), Candida parapsilosis in two (1.3%), and Candida lipolytica in one (0.7%) isolate. Candida species was significantly associated with clinical types, episode types, pain on swallowing, CD4 count, and antiretroviral (ARV) use among all patients. Conclusion Among HIV/AIDS patients with OC, growth of C. albicans only was more common in higher CD4 count, while mixed growth of C. albicans and C. non-albicans was more common in lower CD4 count. Clinical features associated with growth of C. albicans only were pseudomembranous type, recurrent OC, absence of pain on swallowing, and patients on ARV, whereas those associated with mixed growth of C. albicans and C. non-albicans were cheilitis type, first-episode OC, presence of pain on swallowing, and ARV-naive patients.